Subgame Perfect Equilibria in Continuous-Time Repeated Games - Mitri Kitti (Aboa Centre for Economics (ACE), 2018)
This paper considers subgame perfect equilibria of continuous-time repeated games with perfect monitoring when immediate reactions to deviations are allowed. The set of subgame perfect equilibrium payoffs is shown to be a fixed-point of a set-valued operator introduced in the paper. For a large class of discrete time games the closure of this set corresponds to the limit payoffs of when the discount factors converge to one. It is shown that in the continuous-time setup pure strategies are sufficient for obtaining all equilibrium payoffs supported by the players' minimax values. Moreover, the equilibrium payoff set is convex and satisfies monotone comparative statics when the ratios of players' discount rates increase.
Keywords: C72; C73; 330; repeated game; continuous time; subgame perfection; equilibrium payoff set